A new Costa Rican species of Drosophila visiting inflorescences of the hemi-epiphytic climber Monstera lentii (Araceae) - Vilela, Carlos (2018)
Drosophila monsterae sp. nov. is described from 11 males and 13 females collected from the inside of closed inflorescences of Monstera lentii (Araceae) at 1810 m altitude in the Forest Reserve of Cerro de La Carpintera, Canton La Unión, Province of Cartago, Costa Rica. Although flies have been seen wandering and copulating inside the floral chambers of closed inflorescences during the floral female phase, eggs or larvae have not yet been found either in the spathe or in the fleshy spadix. The new species is related to Drosophila tristani Sturtevant, 1921, from San José Costa Rica, from which it differs mainly by having smaller slightly circular compound eyes, distinctly broader genae (cheek index ca. 2.4 vs 5 in D. tristani), and the inner capsule of spermathecae with an unusual folded duct at basal half of its very wide introvert. This is the eighth species to be included in the New World, essentially Neotropical, subgenus Phloridosa. Photomicrographs of male and female terminalia are also provided. © 2018 Sociedade Brasileira de Entomologia